1983
DOI: 10.1071/ea9830116
|View full text |Cite
|
Sign up to set email alerts
|

The effects of levamisole treatments and cobalt bullet therapy on the performance of yearling beef cattle in south-east Queensland

Abstract: The effect of levamisole treatment every 3-4 weeks, cobalt therapy, or both, on the performance of yearling cattle grazing together on known cobalt-deficient pastures on a siliceous sandy soil in south-eastern Queensland was studied between August 1978 and October 1979. In the first stage of the observations, from August to March, the responses (Pc0.05) in liveweight gain compared with the controls (C) were 18, 54 and 75 kg for levamisole (L), cobalt bullets (B), and both (LB) respectively. Thus the responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Trace element deficiencies found or suspected of limiting livestock productivity in northern Australia include Cu deficiency over extensive areas of Queensland and the Northern Territory (Gartner et al 1980;Murphy et al 1981;Wesley-Smith and Schlink 1990), Co deficiency along the coastal areas of Queensland (Nicol et al 1983;Rosbrook et al 1992) and in restricted areas of the Northern Tablelands of New South Wales (Duncan et al 1986), Se deficiency in the central and coastal areas of Queensland (K. McGuigan pers. comm.)…”
Section: Trace Elementsmentioning
confidence: 99%
“…Trace element deficiencies found or suspected of limiting livestock productivity in northern Australia include Cu deficiency over extensive areas of Queensland and the Northern Territory (Gartner et al 1980;Murphy et al 1981;Wesley-Smith and Schlink 1990), Co deficiency along the coastal areas of Queensland (Nicol et al 1983;Rosbrook et al 1992) and in restricted areas of the Northern Tablelands of New South Wales (Duncan et al 1986), Se deficiency in the central and coastal areas of Queensland (K. McGuigan pers. comm.)…”
Section: Trace Elementsmentioning
confidence: 99%
“…In a review, Gardiner (1977) stated that "although not yet clear cut, a plasma level of B12 of about 150 pg/ml (110 pmolilitre) may be expected to be associated with noticeable deficiency signs in cattle, and around 100 pg/ml (74 pmolilitre) with frank deficiency". Nicol et al (1983) reported mean serum vitamin B 12 levels of 10 and 19 pmolilitre in untreated cattle during a period of growth response to cobalt supplementation. However, Reid & McQueen (1985) reported no responses at serum concentrations of 61-70 pmolilitre, whereas McPherson (1981) noted serum vitamin B12 concentrations as low as 37 pmolilitre without evidence of a growth response to supplementation.…”
Section: Introductionmentioning
confidence: 99%